CONSCIOUSNESS TO LIBERATE: In Search of the Political Paradigm of Muhammadiyah - Ridho Al-Hamdi (Journal of Contemporary Islam and Muslim Societies, 2021)
Abstract: This paper examines the political paradigm of Muhammadiyah in thinking and behaving because Muhammadiyah can survive to surpass political impediments for more than a century ago. Methodologically, it is qualitative research by utilising documentary study and in-depth interviews as the data-gathering technique. The finding demonstrates that “consciousness to liberate” is the political paradigm of Muhammadiyah. This paradigm has three interrelated dimensions: transcendental dimension, humanistic dimension, and modernity dimension. The former indicates the prophetic consciousness, the middle demonstrates the liberation theology, and the latter denotes the values Muhammadiyah’s goal. Therefore, the Muhammadiyah consciousness to strives for prophetic missions not merely restricted to liberate humankind from colonisation, oppression, backwardness, and poverty but also to liberate mustadh‘afin from unfair policies and liberal systems. Keywords: Muhammadiyah, consciousness, political paradigm, liberation, al-Mâ‘ûn